Acetate-assisted increase of butyrate production by Eubacterium limosum KIST612 during carbon monoxide fermentation. (December 2017) - Park, Shinyoung; Yasin, Muhammad; Jeong, Jiyeong; Cha, Minseok; Kang, Hyunsoo; Jang, Nulee; Choi, In-Geol; Chang, In Seop
Highlights: Significant improvements were achieved in acetate-assisted cultivation. The main product was shifted from acetate to butyrate. Three possible routes to acetate assimilation and energy conservation were suggested. An efficient way for more reduced biochemical products can be suggested. Abstract: The acetate-assisted cultivation of Eubacterium limosum KIST612 was found to provide a way for enhancing cell mass, the carbon monoxide (CO) consumption rate, and butyrate production using CO as an electron and energy source. Cell growth (146%), μ max (121%), and CO consumption rates (151%) increased significantly upon the addition of 30 mM acetate to microbial cultures. The main product of CO fermentation by E. limosum KIST612 shifted from acetate to butyrate in the presence of acetate, and 5.72 mM butyrate was produced at the end of the reaction. The resting cell experimental conditions indicated acetate uptake and an increase in the butyrate concentration. Three routes to acetate assimilation and energy conservation were suggested based on given experimental results and previously genome sequencing data. Acetate assimilation via propionate CoA-transferase (PCT) was expected to produce 1.5 mol ATP/mol butyrate, and was thus anticipated to be the most preferred route.